Occurrence and partitioning of selected micropollutants in the Ishmi River Basin, Albania: water treatment under use of low-cost functionalized magneto clay-biochar composites for naproxen, carbamazepine, Cd(II), Cr(VI), and Cu(II) removal - Peqini, Aleksandër; Justus Liebig University Giessen (My University, 2026)
This cumulative study explores the occurrence, environmental behavior, and removal of heavy metals and pharmaceuticals (belonging to the group of “micropollutants”) through the development of sustainable adsorbents in aquatic systems, with a focus on the Ishmi River basin, Albania. In the first component of this thesis, twelve pharmaceuticals, including caffeine (CAFF), anti-inflammatories (naproxen (NPX), ibuprofen (IBU), and diclofenac (DCF)), antibiotics (anhydro-erythromycin (AETM), azithromycin (ATM), clindamycin (CMC), ciprofloxacin (CFC), erythromycin (ETM), sulfamethoxazole (SMX), and trimethoprim (TMP)), and the antiepileptic carbamazepine (CBZ) were analyzed in surface water and sediment during seasons of the years 2023 and 2024. Highest concentrations occurred near urban areas with limited wastewater treatment, notably at site LR1. Partitioning behavior (Kd, Koc) was significantly influenced by compound-specific (Dow, molecular weight) and sediment-specific (pH, content of organic carbon, CaCO3, and metals) properties, and regression models successfully predicted partition coefficients for NPX, IBU, CFC, AETM, and CMC. In the second component, innovative low-cost magneto-biochar-clay (MBC) composite adsorbents were prepared from the combination of magnetic nanoparticles, biochar (from grape cluster stalk), and feldspar clay and were tested for simultaneously heavy metal removal (Cd(II), Cr(VI), Cu(II)). The MBC 1:2:1 and MBC 1:3:1 showed high adsorption capacities due to enhanced surface area and functional groups. Adsorption was governed by electrostatic interactions and pore filling, with Cr(VI) showing the highest removal efficiency and strong adsorbent reusability over multiple cycles. The third component evaluated the MBC 1:2:1 composite for pharmaceutical removal, specifically NPX and CBZ. The composite demonstrated excellent adsorption performance (≥99% efficiency over five cycles), particularly at low pH values, through electrostatic and hydrophobic interactions. NPX removal remained high (≈93%) even in real Ishmi River water. Overall, the combined findings highlight the influence of environmental and sediment characteristics on pharmaceutical distribution, both the environmental risks posed by pharmaceutical and metal contaminants in under-monitored regions and the effectiveness of MBC composites as sustainable, cost-effective adsorbents for water treatment applications.
Keywords: Emerging contaminants; Sediment-water partitioning; Adsorption; Magneto-biochar-clay composites; Organic contaminants; Heavy metals; Water treatment; ddc:333.7